LAPORAN KASUS: PERBANDINGAN PROSEDUR CUTLER BEARD DAN DIRECT CLORUSE PADA DEFEK PALPEBRA YANG LUAS AKIBAT TRAUMADI RSU DR. SAIFUL ANWAR MALANG - Kurniawan, M. Iwan; Sadono, Elfina G (Fakultas Kedokteran Universitas Brawijaya, 2007)
The paper aimed to report a different management ofreconstruction for large traumatic upper eyelid defect. Case 1 : a 17 years old woman with traumatic upper eyelid defect in the right eye since 2 years old. The defect was linear but wide, looks like a triangle defect. Defect had repaired by direct closure. After the operation the defect remain. Case 2 : a 45 years old man with more than 50 % traumatic upper eyelid defect in the left eye. Cutler-beard procedurwas made to close the defect. Separation of the flap had been done at the second procedure. Cutler-beard procedure, done to the second patient, had succed to close the upper eyelid defect. Reconstruction procedure carried out for the first patient was not adequate to restore the large upper eyelid defect. Cutler-beard procedure is used for upper eyelid defect involving more than 50% seem to have a good result.Key words: Cutler beard, Direct closure